THE IMPORTANCE OF THE ROLE OF AN APPROPRIATE CURRICULUM IN EDUCATION - Sa'dullah, A.; Imami, Agus Sulthon; Khaer, Abu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The curriculum plays a vital role in education as a guide for future educational goals so that it runs better and optimally. The application of the curriculum developed in schools to suit the circumstances and needs of the environment because these things are related to each other in it and become a reference for all parties who play a role in implementing the applicable curriculum. The curriculum process includes planning, organizing, implementing, monitoring and evaluating, in building a good curriculum certainly requires in-depth study and thought. Evaluation as the final process of a curriculum is used as a benchmark for curriculum achievement. Education is a human effort to increase knowledge obtained from formal and informal institutions. To achieve this, appropriate educational goals are needed. The purpose of education will determine success in forming the human person, balanced with other elements in education. The purpose of writing this article is to analyze the critical role of the curriculum in achieving educational goals.